Toughening mechanisms of SiC-bonded CNT bulk nanocomposites prepared by spark plasma sintering. (February 2018) - Dolati, Sina; Azarniya, Amir; Azarniya, Abolfazl; Eslami-shahed, Hossein; Hosseini, Hamid Reza Madaah; Simchi, Abdolreza
Abstract: In this work, silicon carbide (SiC) was utilized as a binding agent to fuse carbon nanotubes (CNTs) into highly tough dense CNT bulk nanocomposites through spark plasma sintering (SPS) method. Phase studies were performed using x-ray diffraction analysis (XRD) and field-emission scanning electron microscopy (FESEM) and obtained results were verified by the microstructural evolution. Also, the optimum processing temperature was determined as 1600 °C at which the undesired allotropic phase transformation of SiC (β) → SiC (α) was avoided and single-walled CNTs (SWCNTs) were structurally preserved. Fracture toughness of the nanocomposite synthesized at optimum processing conditions was determined by Vickers indentation method equal to 13.3 MP·m 1/2 . Toughening mechanisms were directly observed throughout the microstructure among which crack-wake bridging by SWCNTs and crack deflection by SiC particles were the most dominant. Graphical abstract: Highlights: SiC is utilized as an appropriate binder for densification of CNT bulk materials. An increase in relative density can be obtained as well as high fracture toughness. 1600 °C is a critical temperature above which β-SiC is transformed to ɑ-SiC. CNTs are preserved up to 1800 °C, but SiC transformation degrades the properties. CNT Bridging and SiC fracture are most dominant toughening mechanisms.